The communicative evaluation of Spanish in non-Spanish-speaking students of the Medical Sciences preparatory course - Adrian Abreus González; Guadalaupe García González; Nancy Castillo Mauri; Zaydelys Lucrecia Torres Calzadilla; Juan Manuel Cala Corrales (Medisur)
Foundation: the linguistic skills’ evaluation in foreign languages has been the subject of study by different researchers. The establishment and identification of indicators that describe the performance of students according to the levels of competence defined by the Common European Framework of Reference for Languages, constitutes a priority for this study. Objective: to describe the linguistic performance of non-Spanish-speaking students in the preparatory course for Medical Sciences students at the Medicine Latin American School. Methods: Qualitative research methods and techniques such as observation and discussion groups were used, through workshops developed with the group of Spanish teachers for foreigners at the Medicine Latin American School and the Cienfuegos University. Results: 57.8% of the students who participated in the study reached level B1 of performance in the use of Spanish as a foreign language, while 31.8% were able to meet the indicators established for level A2 and only 18 of the students who took part in the study were classified at level A1, which represents 8%. The most frequently errors found in students are related to poor vocabulary, both in oral and written communication. At the same time, listening comprehension constitutes the skill that had the most negative impact on student performance, due to the non-existence of some Spanish phonemes in the mother tongue of some non-Spanish-speaking students. Conclusions: Although the largest number of students achieved high levels of performance in the use of the language, there are still difficulties, especially in vocabulary poverty.